Play as a Way to Learn and Have Fun (2014)
Two children participating in Expeditions to Knowledgewere interviewed with knowledge about the importance of the game in their daily lives and in the program and regarding the responses of both it is concluded that playing is one of the best activities to encourage curiosity and generate fun learning.